A Study of Emotions in Sport Psychology Based on The Mood State Inventory - Xiong Haoran, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
This paper analyzes the emotional results of sports psychology by conducting an in-depth study and analysis of emotions in the form of a state of mind scale. This study takes the research on the effect of sports on an individual’s state of mind as the background, and the different effects of different sports on the state of mind of college students as the entry point. To achieve this, it uses a combination of the literature method, questionnaire survey method, experimental method, and mathematical and statistical methods. A total of 348 students are selected as experimental subjects, respectively, for 10 weeks of physical exercise in different sports, and their state of mind is measured twice before and after the experiment. The difference test is conducted on the measured state of mind data. Through the comparative study of the changes in the state of mind of college students who participate in different sports, this paper is able to analyze the effects of different sports on the state of mind of college students in different directions and to different degrees, which can help college students choose the sports that are suitable for them, provide a practical reference for sports to improve the state of mind of college students and promote their physical and mental health development. The mechanism of this predictive effect is mainly the indirect effect of internal motivation and intention to exercise, i.e., the self-comparison attention of college students cannot directly affect their exercise persistence but can promote their exercise persistence through the indirect path of enhancing their internal motivation and intention to exercise. To ensure the positive effect of the intervention of physical test self-comparison on college students' exercise persistence, it is necessary to focus on the mediating role of exercise internal motivation and exercise intention in their relationship.